Kondisi Padang Lamun Hubungannya Dengan Jenis Substrat di Desa Maitara Selatan dan Induk Kota Tidore Kepulauan - Ariyanto M. Ali; Ainuddin Ainuddin; Nuraini Adung Damsiki (Peneliti.net, 2021)
Seagrass bed is a true flowering, fruiting, leafy and rooted plant that grows on a muddy, sandy to rocky substrate that lives submerged in shallow and clear sea water, with good water circulation. This study aims to determine the diversity of seagrass species, sdeagrass unioformity, dominace index, seagrass density, and percentage of seagrass cover, ass well as the effect of substrate types on seagrass conditions in the waters of Maitara utara village and Maitara induk village. This research is divided into two observation stations based on the distribution of seagrass,namely station I in Maitara selatan village and station II in Maitara induk village. At each station it is divided into three lines an three quadrants, the distance of 60 meters where on each line the transect line from the coastline to the sea is 60 meters long, while the distance of each quadrant I, II, III with a distance of 20 meters. Measurement of oceanographic factors includes traffic, turbidity, current velocity, temperature water pH and sediment. Furthermore, it was tested by simple linear regression using excel version 2010 to determine the relationship between seagrass and the types of sediment grains. The results of this study indicate that the conditions of seagrass density at stations I and II belong to the scale of dense conditions (125-175) and very dense (> 175). The Diversity Index at both stations is classified as moderate diversity. The seagrass uniformity index at stations I and II is classified as a high level of uniformity, and the dominance index obtained at stations I and II is classified as a low level of dominance. The correlation between substrate grain diameter and seagrass at stations I and II does not have a strong linear relationship, the r (correlation) value is obtained at station I of 0.037 and at station II of -0.145 which means that the seagrass density has a negative correlation with the type of substrate grain